Issues relating to pre-adjudication of industrial disputes - Kamal Halili Hassan (Fakulti Undang - Undang, 2006)

(untitled)
In Malaysia parties to industrial disputes are non free to file their cases directly to the Industrial Court. They have to first adhere and observe certain requirements of pre adjudication process. This is because Malaysian laws and policies viewed industrial disputes as having serious ramifications on the industry if they are not properly handled. This before disputes are to adjudicated by the Court, they need to undergo certain processes such as conciliation. Conciliation is part of the Alternative Dispute Resolution mechanism and it has been widely used in the settlement of industrial disputes. Even the executives (represented by the Minister) have the power to sieve the cases before they reached the Industrial Court. This article thus discusses three main issues of pre adjudication process, namely, conciliation, the power of the Minister to refer a case or otherwise to the Industrial Court and his reasons, if any, for not referring a case to the Court. All three issues are coherently analyzed into a single theme, namely, the pre adjudication process of industrial disputes